2018
DOI: 10.1371/journal.pone.0205233
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of GeneXpert and LED-FM for diagnosis of pulmonary tuberculosis: A systematic review

Abstract: BackgroundEarly and accurate diagnosis of tuberculosis is a priority for TB programs globally to initiate treatment early and improve treatment outcomes. Currently, Ziehl–Neelsen (ZN) stain-based microscopy, GeneXpert and Light Emitting Diode-Fluorescence Microscopy (LED-FM) are used for diagnosing pulmonary drug sensitive tuberculosis. Published evidence synthesising the cost-effectiveness of these diagnostic tools is scarce.MethodologyPubMed, EMBASE and Cost-effectiveness analysis registry were searched for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…The WHO initially recommended this technology in early 2011 [67]; the organization is monitoring the global rollout of this method to promote coordination [107]. In the past 3 years, one systematic and four literature reviews of the performance of GeneXpert MTB/RIF for the diagnosis of TB in several settings have been published [108–112]. Because comprehensive reviews on the diagnostic accuracy of the GeneXpert MTB/RIF system were published in 2013 [113], 2014 [114] and 2019 [103], we have not focused on this topic here.…”
Section: Detection Of M Tuberculosismentioning
confidence: 99%
“…The WHO initially recommended this technology in early 2011 [67]; the organization is monitoring the global rollout of this method to promote coordination [107]. In the past 3 years, one systematic and four literature reviews of the performance of GeneXpert MTB/RIF for the diagnosis of TB in several settings have been published [108–112]. Because comprehensive reviews on the diagnostic accuracy of the GeneXpert MTB/RIF system were published in 2013 [113], 2014 [114] and 2019 [103], we have not focused on this topic here.…”
Section: Detection Of M Tuberculosismentioning
confidence: 99%
“…The reporting quality of the three published studies was assessed against 24 checkpoints using the CHEERS statement 22. The risk of bias for the three published studies was assessed using the 20-item CHEC-extended checklist 24 32. A risk of bias assessment using the CHEC-extended checklist was not performed for the ACSQHC report; rather, the quality of the ACSQHC report was assessed against 14 checkpoints using the AACODS checklist 23.…”
Section: Resultsmentioning
confidence: 99%
“…Out of a maximum total score of 20, Woolley et al scored 16 (80%) and both Hollenbeak et al and Thanh et al had reported 17 (85%) of items in the CHEC-extended checklist (see online supplementary appendix table S4). Overall, the risk of bias across the three studies as appraised using the CHEC-extended list ranged from moderate to low 24 32…”
Section: Resultsmentioning
confidence: 99%
“…GeneXpert MTB/RIF has been widely deployed in a range of LMIC settings and appears to be cost-effective in at least some of them. [29][30][31] However, even this system shares the challenge presented by low copy number bacteria, which may certainly be the case in paucibacillary mycobacterial disease. Potential solutions to insensitivity include new technologies and applications of nucleic acid-based methods such as single-cell whole genome sequence Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)-based detection 32 as well as free DNA capture as applied in fetal abnormality and cancer screening tests.…”
Section: Promises and Pitfalls Of Nucleic Acid Amplification Testsmentioning
confidence: 99%